Uji Diagnostik Lipoarabinomannan Urin untuk Deteksi Mycobacterium tuberculosis pada Pasien Dengan dan Tanpa Infeksi HIV - Andriana Kirana Puspa; Dean Handimulya (Indonesia Journal of Chest Critical Emergency Medicine, 2025)
Background Most of the tuberculosis (TB) diagnostic tests rely on sputum samples, which are often difficult to obtain in children, patients with extrapulmonary TB and people living with Human Immunodeficiency Virus (PLHIV). Lipoarabinomanan (LAM), a major component of the Mycobacterium tuberculosis (Mtb) cell wall, function as a virulence factor and can enter the systemic circulation during infection. Due to its relatively small molecular size, LAM is filtered by the kidneys and can detected in urine. Detection of urinary LAM antigen offers a non invasive and rapid diagnostic approach that can be performed as appoint of care test (POCT), providing a promising tool for TB diagnosis, especially in individuals with difficulty producing sputum or those who are immunocompromised, such as PLHIV. Method A cross-sectional study was conducted at dr. Cipto Mangunkusumo National General Hospital involving 96 subjects with suspected tuberculosis (TB), with or without Human deficiency Virus (HIV) infection. Urine samples were tested using Abbott Determineä TB LAM Ag, a lateral flow immunoassay for detecting lipoarabinomannan antigen. Diagnostic performance was compared with a composite reference standard, define as appositive result in at least one of the following tests: real time polymerase chain reaction (RT-PCR), acid-fast bacilli smear, or acid-fast bacilli culture. Numeric data were tested for normality using Kolmogorov-Smirnov test and presented as median (range), while categorical data were expressed as absolute frequency (n) and percentage (%). Diagnostic performance was assessed in terms of sensitivity, specifity, predictive values, and accuracy. Result Among 96 subjects, the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of the urinary LAM test compared with bacteriological TB results were 51%, 68%, 46%, and 73%, respectively. In 33 participants with HIV infection, the sensitivity, specificity, PPV, and NPV were 54%, 59%, 40%, and 72%, respectively. In 63 participants without HIV, the sensitivity and PPV were both 50%, while specificity and NPV were 73%. The urinary LAM test demonstrated moderate diagnostic performance, with slightly higher sensitivity among patients with HIV infection compared to those without. CONCLUSION: The urinary LAM test is a rapid and simple diagnostic tool for tuberculosis. It demonstrated moderate diagnostic performance, with higher sensitivity among patients with HIV infection compared to those without, suggesting greater utility as an adjunct diagnostic test in this population. Keywords: Human Immunodeficiency Virus, Lipoarabinomannan, Tuberculosis, Point of care testing, Urine